THE INFLUENCE OF WORK MOTIVATION, SUPERVISION AND LEADERSHIP ON WORK DISCIPLI - Eni Mawarsih; Radiman Radiman (Proceeding International Seminar of Islamic Studies, 2022)
The purpose of this study is to find out and analyze the influence of work motivation on work discipline, to find out and analyze the influence of supervision on work discipline, to find out and analyze the influence of leadership on work discipline, to find out and analyze the influence of work motivation, supervision and leadership together on work discipline at PT. Wahana Trans Lestari Medan. This research uses an associative approach, which is research conducted to determine the influence or relationship between free variables and bound variables. The population and samples in this study were all employees of PT. Wahana Trans Lestari Medan which has a total of 43 people. The data collection technique used in this study was a questionnaire. The data analysis technique used is multiple linear regression analysis. The results of this study show that partially motivation has an influence on work discipline. Partially supervision has an influence on labor discipline. Partial leadership has an influence on work discipline, and simultaneously work motivation, supervision, and leadership have a significant influence on work discipline in pt. Wahana Trans Lestari.